2015
DOI: 10.1158/1055-9965.epi-14-0967
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Fear: Facilitator and Deterrent to Participation in Colorectal Cancer Screening

Abstract: Background: Cancer fear has been associated with higher and lower screening uptake across different studies, possibly because different aspects of cancer fear have different effects on intentions versus behavior. The present study examined associations of three aspects of cancer fear with intention and uptake of endoscopic screening for colorectal cancer.Methods: A subsample of UK Flexible Sigmoidoscopy (FS) Trial participants received a baseline questionnaire that included three cancer fear items from a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 21 publications
5
87
0
1
Order By: Relevance
“…A reliable positive association has been demonstrated between fear and breast self-exam or mammography [19]. Fear and worry have been shown to increase intention but not uptake in CRC screening [20]. Likewise, fear was sited as a significant psychological determinant of prostate cancer screening [21].…”
Section: Discussionmentioning
confidence: 97%
“…A reliable positive association has been demonstrated between fear and breast self-exam or mammography [19]. Fear and worry have been shown to increase intention but not uptake in CRC screening [20]. Likewise, fear was sited as a significant psychological determinant of prostate cancer screening [21].…”
Section: Discussionmentioning
confidence: 97%
“…The role of emotions and coping strategies in CRC screening behaviour has been previously reported. A questionnaire study of a subsample of the UK FS trial participants, for example, concluded that finding thoughts about cancer uncomfortable is associated with lower screening uptake and that different aspects of cancer fear can facilitate and inhibit screening intention and behaviour in different ways 22. The accounts from our participants illustrate and contextualise the strong emotions that can result from receiving a screening invitation associated with concerns not only about the screening process, but also with a potential cancer diagnosis and outcome expectancies associated with treatment beliefs and, for a small minority, general anxiety associated with hospital attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research among participants in the UK FS Trial1 has identified that most of the effects of demographic and health variables on interest in participation are mediated by sociocognitive variables,18 although actual uptake among interested participants is influenced more directly by demographics, health and stress 19. Non-participation is also reported to be influenced by avoidant attitudes towards screening, other health beliefs,20 21 fear22 and deprivation 23. This research has been undertaken with people offered screening within a research trial context or has focused on intention rather than actual screening behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Taking such a tool, typically used only in Primary Care settings [24,25] and offering it to public in a guided way might be a way to address the fear of cancer [15][16][17]. In addition, this research shows that individuals show a will to understand their symptoms better and appreciate the ability to subsequently verify if those symptoms could be cancerous.…”
Section: Perceptions and Attitudes In Relation To Community-based Canmentioning
confidence: 98%
“…As cancer appears to be one of the most feared diseases in the UK and USA [15][16][17] and a cancer diagnosis is often life changing [18], individuals may avoid considering this issue by downplaying their own cancer risk or ignoring symptoms. Therefore, any intervention offered to the public should aim to minimize potential anxiety, at the same time showing early cancer detection in a positive light.…”
Section: Introductionmentioning
confidence: 99%